Pengaruh Kompetensi dan Pengembangan Karir terhadap Kinerja Pegawai Melalui Motivasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Tanjung Jabung Timur - Syahputra, Sofyan Hadi; MS, M. Zahari; Akbar, Ali (J-MAS (Jurnal Manajemen dan Sains), 2025)
The purpose of this study is to analyze the influence of competence and career development on employee performance through motivation at the Public Works and Spatial Planning Agency of Tanjung Jabung Timur Regency. The methods used in this study are descriptive verification and quantitative methods. The object of research in this study is the Influence of Competence and Career Development on Employee Performance Through Motivation at the Public Works and Spatial Planning Office of Tanjung Jabung Timur Regency. Based on the approach, it can be seen that the number of samples is 62 people. This study uses the PLS analysis method. The results of the study show that Competence has a positive and significant effect on motivation, Career development has a positive and significant effect on motivation Competence does not have a significant effect on employee performance, Career development has a positive and significant effect on employee performance, Motivation has a positive and significant effect on employee performance, Competence has a positive and significant effect on performance through work motivation and Career development has a positive and significant effect on performance through work motivation. For further research related to the study, it is hoped that further researchers will add other variables that can theoretically affect employee motivation and performance.